Dari Murabahah Menuju Musyarakah, Upaya Mendorong Optimalisasi Sektor Riel - Muhammad Akhyar Adnan (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2005)
The murabahah products have been dominating Sharia Bank Products portfolio. There is nothing to be objected, when this phenomenon is seen from the fiqh point of view and bank opera¬tion policies. However, some concerns might be raised since some hidden risks can be predicted. The choice of murabahah over other products has brought some risks such as an opera¬tional bias of murabahah as it has been condemned considerably in practices, as well as a concern of dif¬ficulty in developing an ideal balance between financial and real sectors in our economy. The last mentioned factor is believed as to be an important factor in Islamic Economics concepts and development.This article is aimed at offering an alternative solution to the dilemmatic situation. The application of musharaka is deemed as to be a considerable solution. It is expected that the will¬ingness of all related parties to accept the solution will create an optimal balance between the financial and real sector in practices. In turn it will develop a stronger economic foundations.Keywords: Murabahah, musharaka, optimal balance, financial and real economic sector.